(untitled) (Global Journal of Management and Business Research, 2017)
This article has the objective to provide a theoretical framework empirical or by a brief literature linking in particular the impact of corruption on economic growth, or the impact of financial development on economic growth, or the overall impact of corruption and of financial development on economic growth. Some studies have shown a positive relationship or negative between these causal relation relations and interaction. This study is estimated on the basis of the annual data relating to five countries BRICS, observed during the period from 2000 to 2012, and using the method of least ordinary square (OLS) of panel dynamic. The results of the estimation show that there is a significant relationship positive or negative between corruption, the financial development and economic growth. This relationship and more and more intense for the role of the institutional framework and the financial system of the BRICS countries.